2020
DOI: 10.1037/tra0000609
|View full text |Cite
|
Sign up to set email alerts
|

China experience from COVID-19: Mental health in mandatory quarantine zones urgently requires intervention.

Abstract: The study investigated the quarantine of COVID-19 and its impact on mental health. The results showed that there was a significant difference in PTSD Checklist for DSM-5 scores between the quarantine group and the non-quarantine group. As a result, the mental health of residents in mandatory quarantine zones urgently requires intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 4 publications
3
30
0
1
Order By: Relevance
“…Increased symptoms of the anxiety-affective cluster were common (prevalence ≥ 30% for worsened irritability, agitation, and apathy and ≥ 20% of new onset sleep disorder and irritability) and were homogeneously reported across disease types. This finding is in line with many observations of increased psychological symptoms of anxiety and depression during COVID-19 quarantine in healthy subjects and give support to the notion that quarantine acts as a stressor event that induces symptoms similar of those reported in the post-traumatic stress disorder (PTSD) ( 22 24 ). Indeed, quarantine due to pandemic involves different social, emotional, psychological, and physical modifications, each one with a potential contribution to increase distress.…”
Section: Discussionsupporting
confidence: 90%
“…Increased symptoms of the anxiety-affective cluster were common (prevalence ≥ 30% for worsened irritability, agitation, and apathy and ≥ 20% of new onset sleep disorder and irritability) and were homogeneously reported across disease types. This finding is in line with many observations of increased psychological symptoms of anxiety and depression during COVID-19 quarantine in healthy subjects and give support to the notion that quarantine acts as a stressor event that induces symptoms similar of those reported in the post-traumatic stress disorder (PTSD) ( 22 24 ). Indeed, quarantine due to pandemic involves different social, emotional, psychological, and physical modifications, each one with a potential contribution to increase distress.…”
Section: Discussionsupporting
confidence: 90%
“…To the best of our knowledge, numerous scholars concentrated on the psychological responses to infectious diseases outbreaks, which were conducted on the groups in hospitals, including patients with SARS/MERS (11,12), medical staff working to combat the illness (e.g., SARS and COVID-19) (13)(14)(15), and survivors of SARS epidemic (16). A previous study reported that 104 residents of Wuhan (under mandatory quarantine) had more severe symptoms of posttraumatic stress disorder (PTSD) than 330 residents of Shanghai (without mandatory quarantine) during the COVID-19 outbreak, although the sample size was relatively small (17). Another study investigated the prevalence of psychosocial problems among the general population under the COVID-19 epidemic and found that Hubei province (eight people) had more severe insomnia and stress symptoms than those who lived in areas outside Hubei province (18).…”
Section: Introductionmentioning
confidence: 99%
“…The freedom of the quarantined person was restricted to control transmissible diseases. PTSD and depression were considerable differences between quarantined groups and non-quarantined groups ( Wu et al., 2020a , b ). It impacts more physiological and psychological problems on the quarantined person.…”
Section: Discussionmentioning
confidence: 93%